A communist and squad leader wrote in a letter to Chairman Mao what he tought about Deng Xiaoping's counter-revolutionary revisionist line
A communist and squad leader wrote in a letter to Chairman Mao what he tought about Deng Xiaoping's counter-revolutionary revisionist line.